Forensic Criminal Investigation Subject Interaction Filtering Tool for Digital Interaction Data (2021)
Some embodiments include a cloud computing system and database management for forensic criminal investigations. The cloud computing system may produce a visual representation of various digital interactions between various individuals. These digital interactions, for example, may include phone calls, text messages, emails, social media messages or posts, etc. between a first individual and a second individual. The visual representation, for example, may be provided on a webpage. The visual representation, for example, may graphically represent a relationship between the first individual and the second individual.